Cystic Degeneration of Uterine Fibroid Mimicking a Malignant Uterine Neoplasm on MRI - Nittala, Pramod Philip; Shukla, Roshni (International Journal of Medicine, 2013)
Uterine leiomyomas or fibroids are the most common neoplasm of the uterus. These are commonly encountered in middle aged women in the reproductive age group. Depending upon the location within the uterus and their size, fibroids can be symptomatic or asymptomatic. The common symptoms are of abnormal vaginal bleeding and pain. Fibroids can undergo secondary changes like hyaline, cystic or red degeneration, calcification and sarcomatous transformation and imaging features in these conditions can mimic different pelvic pathologies.